Global distribution of rice weeds – A review. (February 2016) - Kraehmer, Hansjoerg; Jabran, Khawar; Mennan, Husrev; Chauhan, Bhagirath Singh
Abstract: This review provides an overview on the most common rice weed species of the world. It shows that a few generalists have established in rice independent from sites, crop management systems, and local climatic conditions. Cosmopolitan weeds are even constant elements where rice cultivation started just a century ago. Local differences may be explained by cultivation methods, growing seasons, or special weed management. Some general changes in weed spectra have been observed globally in recent years. Weedy rice ( Oryza sativa L.) and herbicide resistance have become general global problems within the last decades. Some global key weed genera such as Echinochloa, Cyperus, Scirpus, or Fimbristylis species are, however, still dominating rice fields despite the decade long use of well performing herbicides. On the other side, general species shifts as a result of resistance have not been observed yet. Leptochloa species started to become major problems in Asia in the end of the last century and now in Europe also. Several modern herbicides allow the control of perennial weeds, such as Cyperus rotundus L. or Eleocharis kuroguwai Ohwi which makes them no longer serious threats. Some genera in rice such as Echinochloa and Oryza (weedy rice) are characterized by an enormous germplasm variability which makes species definitions difficult. The fact that weeds in rice have to adapt to wet or aquatic conditions reduces the biodiversity range in comparison to other arable crops. Water management has a considerable impact on weed spectra. The increase of rice acreages with reduced irrigation may end up in higher weed infestations. Long term results of weed surveys in rice as they exist for other crops are, however, not available. This makes predictions on biodiversity changes in this crop quite difficult. Graphical abstract: Highlights: The distribution of the most common rice weeds is documented in tables and figures. Many dominant weeds were problems already 30 years ago. Leptochloa species seem to become increasing problem weeds in several parts of the world. A few weeds in rice are not well defined taxonomically such as Echinochloa species and weedy rice biotypes. The increase of rice acreages with reduced irrigation may end up in higher weed infestations and new dominant species.